INSIGHT OF METHANOLIC EXTRACT OF VENTILAGO MADERASPATANA LEAVES ON HEPATOPROTECTIVE ACTIVITY UNDER STREPTOZOTOCIN-INDUCED DIABETIC RATS - REDDY B, VENUGOPAL; REDDY M, RAMANA; SUBBAIAH G, VENKATA; REDDY K, SATHYAVELU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The methanolic leaf extract of Ventilago maderaspatana (MEVML, 200 mg/kg body weight [b.w.]) was investigate to hepatoprotective activity under streptozotocin-induced (45 mg/kg b.w.) diabetic (Di) rats. Methods: In the present study, we determined the blood glucose levels, b.w., insulin, creatinine, and bilirubin levels in normal, Di, Di treated with MEVML and positive control rats. Results: The Di rats shown adverse changes in blood glucose levels, b.w., insulin, creatinine, and bilirubin levels when compared to other group rats. Reverse the adverse changes in the above parameters when treated the Di rats with MEVML Conclusion: The MEVML shown anti-diabetic activity and reverse the adverse changes in the above parameters in liver so that the MEVML supported the traditional claim of the hepatoprotective activity under Di condition.